Pola Penggunaan Antibiotik Profilaksis pada Pasien Bedah Caesar (Sectio Caesarea) di Rumah Sakit Pekanbaru Medical Center (PMC) Tahun 2014 - Husnawati Husnawati; Fitra Wandasari (Jurnal Sains Farmasi & Klinis, 2016)
The research has been done on the use of prophylactic antibiotics in caesarean section at Pekanbaru Medical Center (PMC) hospital in 2014. The aim of this study was to overview the use of prophylactic antibiotics caesarean section. Type of research was an observational study designed a descriptive by conducting a review of the medical records of patients that using prophylactic antibiotics in cesarean section during Januari until December 2014. The samples used were 73 patients who met the inclusion criteria with purposive sampling. The results of this study suggest that the use of prophylactic antibiotics in cesarean section at Pekanbaru Medical Center hospital is a single-dose Ceftriaxone 1g (58.9%) and a combination of gentamicin (80 mg) with Ceftriaxone (1g) (41.1%), where all the form generic drugs (100%) with the time of prophylactic antibiotics for the majority that is 0-2 hours before surgery (100%) with the intravenous route (100%).